Evolution of biventricular T1 values in patients with right-sided congenital heart disease. (8th February 2021) - Burdet, O; Pavon, AG; Bouchardy, J; Blanche, C; Monney, P; Hugelshofer, S; Schwitter, J; Rutz, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Conflicting reports exist on the prevalence and clinical impact of interstitial fibrosis in right ventricular (RV) congenital heart disease (CHD). This study evaluates the longitudinal evolution of native myocardial T1 relaxation time (T1) in RV CHD. Methods: On a 1.5T scanner, an ECG-triggered modified Look-Locker inversion recovery sequence (scheme 3(3)3(3)5) was acquired on a short-axis basal slice covering the RV and left ventricle (LV) on two consecutive CMR exams. Global and segmental (LV = 6, RV = 4) RV and LV T1 values  were calculated (Figure). Results: Mean time between CMR exams for 36 included patients (age 34 ± 2y) was 22 ± 2 months. All LV segments and 81/88% of RV segments of first and second CMR could be analyzed, respectively.  T1 increased mildly but not significantly (table). There was no relationship of T1 to pulmonary regurgitation fraction, pulmonary stenosis or RV enddiastolic volume (p > 0.05). Global RV T1 of the second CMR was related to RV ejection fraction (RVEF): r = 0.353, 3.0 ± 1.4, p = 0.038. T1 of the infero-septal LV segment of first and second CMR, global LV T1 of second CMR and increase of T1 of global LV, anterior, antero-lateral and –septal LV segments, were related to age at CMR: r = 0.333 - 0.463, p < 0.05, respectively. Conclusions: Native T1 values increased mildly in patients with stable RV CHD, which was not statistically significant probably due to the short to median follow-up. Global RV T1 appears to be related to RVEF which could be sign of increasing interstitial fibrosis whereas the relationship of LV T1 to age might be a physiological finding.